Fluctuating velocity measurements in the turbulent wake of a wind turbine model - Wittwer, Adrián Roberto (2018)
Fil: Wittwer, Adrián Roberto. Universidad Nacional del Nordeste. Facultad de Ingenieria; Argentina.